The forensic aspects of suicide and neurotrophin factors: a research study - De Simone, Stefania; Alfieri, Letizia; Bosco, Maria Antonella; Cantatore, Santina; Carpinteri, Michele; Cipolloni, Luigi; Neri, Margherita (Frontiers in Pharmacology, 2024)
Suicide represents a significant public health problem whose neurobiology is not yet fully understood. In many cases, suicidal behavior and psychiatric spectrum disorders are linked, in particular, to major depression. An emerging pathophysiological hypothesis underlines the role of neurotrophic factors, proteins involved in neurogenesis, in synaptic plasticity in response to stressors. Our research aims to evaluate the degree of expression of brain neurotrophic factor (BDNF) in brain areas involved in depressive disorder in suicidal subjects. Furthermore, we want to evaluate the expression of glial cell line-derived neurotrophic factor (GDNF) in suicidal subjects. We selected twenty confirmed cases of suicide among subjects with a clinical history of depressive pathology and possible psychopharmacological treatment, compared to ten controls of individuals who died of non-suicidal causes. For all selected cases and controls, immunohistochemical investigations were performed using a panel of antibodies against the BDNF and GDNF antigens on samples from the various brain areas. The results show that BDNF was under-expressed in the cerebral parenchyma of subjects who died by suicide compared to controls, while there was an overexpression of GDNF in suicide victims, these data could be useful for a clinical application as potential markers for suicidal risk, to assess the severity of depression and development of specific pharmacological therapies for depression.